M6A RNA modification: focusing on non-small cell lung cancer progression, therapeutic strategies and challenges - Yan, Yuyang; Yin, Jiarui; Ding, Quan; Lu, Yan; Gou, Shuhua; Xu, Xi; Li, Yulin (Frontiers in Oncology, 2025)
N6-methyladenosine (m6A) modification is a pivotal mechanism in RNA epigenetics, with profound implications for lung cancer (LC) biology. This review synthesizes current knowledge on m6A’s multifaceted regulatory networks in non-small cell lung cancer (NSCLC), elucidating its roles in tumor proliferation, apoptosis, invasion, and metastasis. We further explore how m6A governs metabolic reprogramming—including glycolysis and ferroptosis—angiogenesis, and tumor microenvironment (TME) remodeling. Additionally, m6A-mediated modification of non-coding RNAs contributes to LC malignancy, underscoring its potential as a diagnostic and prognostic biomarker. These findings also offer novel strategies to overcome therapeutic resistance, a critical challenge in NSCLC treatment. Despite its promise, clinical translation of m6A-targeted interventions faces hurdles, such as the lack of standardized detection methods, the complexity of m6A-associated regulatory networks, and unresolved crosstalk with other RNA modifications. Future research should prioritize multi-omics approaches to resolve these challenges and advance m6A from mechanistic discovery toward clinical application. By addressing these gaps, m6A modulation may emerge as a transformative avenue in precision oncology.